Expression of An Immunogenic Intimin Fragment of EHEC O157:H7 in Escherichia coli Periplasm under The Control of A Rhamnose-Based Regulated Promoter - Hariyatun, Hariyatun; Suwanto, Antonius; Kusharyoto, Wien (BRIN, 2014)
Intimin is the main adhesin of Enterohemorrhagic E. coli (EHEC) O157:H7 bacteria which are the most common leading infectious cause of bloody diarrhea and acute kidney failure in children who develop hemolytic uremic syndrome (HUS). Intimin is required for persistent bacterial colonization to eukaryotic host cell and its receptor-binding activity is localized at the C-terminus 282 amino acids (Intimin282). Thus, Intimin282 is an attractive antigen candidate that could be useful in vaccine and diagnostic systems against EHEC infections. Previous studies had reported expression of Intimin in E. coli cytoplasm using commonly used prokaryotic expression systems. However, it usually encountered several problems, i.e. low expression level, leaky expression, inclusion body formation, and truncated protein. The pRHA vector, which is tightly regulated by Lrhamnose and D-glucose, represents a viable alternative E. coli expression system to overcome such problems. Moreover, E. coli periplasm has an advantage of maintaining protein functionality by providing an oxidative environment that is more efficient than cytoplasm. However, to date there is no study about Intimin expressionusing pRHA expression system and/or in E. coli periplasm. Accordingly, we constructed a recombinant pRHA vector harbouring the respective gene to investigate the expression of an immunogenic Intimin fragment of EHEC O157:H7 in E. coli periplasm. The gene encoding His6-tagged Intimin282 (Int282) together with pelB signal sequence was cloned into the pRHA vector, subsequently expressed in E. coli JM109 and purified. Expression and purification of Int282 were verified by SDS-PAGE and Western blot. The result showed that Int282 was successfully expressed in E. coli periplasm with a protein size of approximately 32 kDa, which corresponded with the predicted size of the protein based on its amino acid sequence.